The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/ijms21093083
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Salivary Protein Adsorption Profile on Titanium and Ceramic Surfaces and the Corresponding Putative Immunological Implications

Abstract: Immune responses triggered by implant abutment surfaces contributed by surface-adsorbed proteins are critical in clinical implant integration. How material surface-adsorbed proteins relate to host immune responses remain unclear. This study aimed to profile and address the immunological roles of surface-adsorbed salivary proteins on conventional implant abutment materials. Standardized polished bocks (5 × 5 × 1 mm3) were prepared from titanium and feldspathic ceramic. Salivary acquired pellicle formed in vitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 65 publications
0
13
0
Order By: Relevance
“…Being quite simple, binary protein solutions are still not very much representative of actual biological fluids. Some researchers moved further on in complexity of systems by investigating through proteomic analysis the exact composition of protein layers adsorbed on several titanium surfaces from real and whole biological fluids such as plasma [ 221 , 228 , 229 ] or saliva [ 230 , 231 , 232 ]. Among the thousands of proteins present in human plasma, the most adsorbed was FN, followed by albumin, alipoprotein, and fibrinogen [ 221 ].…”
Section: Protein Co-adsorption and Competition For The Surfacementioning
confidence: 99%
See 1 more Smart Citation
“…Being quite simple, binary protein solutions are still not very much representative of actual biological fluids. Some researchers moved further on in complexity of systems by investigating through proteomic analysis the exact composition of protein layers adsorbed on several titanium surfaces from real and whole biological fluids such as plasma [ 221 , 228 , 229 ] or saliva [ 230 , 231 , 232 ]. Among the thousands of proteins present in human plasma, the most adsorbed was FN, followed by albumin, alipoprotein, and fibrinogen [ 221 ].…”
Section: Protein Co-adsorption and Competition For The Surfacementioning
confidence: 99%
“…Among the thousands of proteins present in human plasma, the most adsorbed was FN, followed by albumin, alipoprotein, and fibrinogen [ 221 ]. From saliva, which contains about 750 different proteins, less than half of them were found on titanium [ 232 ], mainly amylase and lysozyme [ 230 ]. The effect of surface modification on the protein pellicle composition was also evaluated.…”
Section: Protein Co-adsorption and Competition For The Surfacementioning
confidence: 99%
“…In another in vitro study, the composition of the salivary pellicle formed on smooth Ti substrates was investigated by MS; the findings showed that 10 salivary proteins had an affinity for the Ti surfaces, 16 among the identified proteins, they found; prolactin‐inducible protein and alpha‐amylase 1, which also were found adsorbed on the Ti substrates tested in the present study. Most recently, 495 different proteins were detected, under in vitro conditions, in the salivary pellicle formed on Ti surfaces exposed to stimulated human saliva, 31 while in another in vitro study, 369 different proteins were detected on the salivary pellicle formed on Ti surfaces 18 . In the present study, the protein extraction protocol and the proteomic analysis allowed the identification of 301 proteins adsorbed on the Ti implant surfaces.…”
Section: Discussionmentioning
confidence: 55%
“…In contrast, less is known regarding the composition of the salivary pellicle formed on marked dental implant surfaces. in vitro studies have frequently reported as principal constituents of the salivary pellicle formed on Ti surfaces proteins like serum albumin, salivary amylase, prolactin‐inducible protein, and cystatin‐SA 16‐18 . However, the salivary pellicle's protein content formed under in situ conditions on Ti implant surfaces has not been thoroughly explored.…”
Section: Introductionmentioning
confidence: 99%
“…Although the peri-implant microbiome is unique, these biofilms establish on the surface of implanted materials in a similar manner to that on the natural dentition. A dental pellicle proteome is formed directly on the implant surface [14,15]. Early colonizing microorganisms then attach to the pellicle via van der Waals forces, electrostatic charges, and specific adhesive proteins [16].…”
Section: Introductionmentioning
confidence: 99%